Pengaruh Intellectual Capital Terhadap Kinerja Keuangan dan Nilai Perusahaan (Studi Pada Perusahaan Makanan dan Minuman Yang Terdaftar di BEI) - Petrus Gani (Politeknik Ganesha Medan, 2022)
This study has objectives to analyze the influence of intellectual capital on financial performance and company value, and also examined the influence of financial performance as an intervening variable on company value. The population of the research is the manufacturing of sub- food and beverage industries listed in 2015-2019 consisted of 20 companies. This study has 12 companies as sample that chosen based on the purposive sampling method. Partial Least Square (PLS) as alternative of SEM and as data analysis technique using SmartPLS 3.3 application. The results of this study indicate that partially VAHU and STVA have a significant positive effect on financial performance. Meanwhile, VACA has no significant positive effect on financial performance. Simultaneously VAHU, STVA, and VACA have significant positive effect on financial performance. On the other side partially and simultaneously VAHU, STVA, and VACA have no directly significant positive effect on company value. But through financial performance.